2017
DOI: 10.13005/ojc/330140
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Anti Mycobacterial Activity of Novel Hydrazones

Abstract: The hydrazone Schiff base analogues namely benzoic acid (4-allyloxy-benzylidene)-hydrazide and its series were designed and synthesized. The structures of newly synthesized compounds were characterized by analytical methods and spectral analysis and subjected to antibacterial and docking studies. The synthesized molecules were subjected to molecular docking studies using enoyl-acyl-carrier protein reductase (NADH) from mycobacterium tuberculosis as the receptor. The docking results confirm the binding affinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…2-Mercapto-4-(4-methoxyphenyl)-6-oxo-1,6-dihydropyrimidine-5-carbonitrile 7 , 2-(allyl-thio)-4-(4-methoxyphenyl)-6-oxo-1,6-dihydropyrimidin-5-carbonitrile 8 , methyl substituted-benzoate 11a–11c , and substituted benzohydrazide 12a–12c were obtained according to the reported procedures. 49,50,53–56…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2-Mercapto-4-(4-methoxyphenyl)-6-oxo-1,6-dihydropyrimidine-5-carbonitrile 7 , 2-(allyl-thio)-4-(4-methoxyphenyl)-6-oxo-1,6-dihydropyrimidin-5-carbonitrile 8 , methyl substituted-benzoate 11a–11c , and substituted benzohydrazide 12a–12c were obtained according to the reported procedures. 49,50,53–56…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of the obtained chloro-derivative 9 with the appropriate acid hydrazides 12a-12c (obtained according to the reported procedures), 49,50 in isopropanol in the presence of TEA yielded the target derivatives 13a-13c. The formation of compounds 13a-13c was confirmed by spectral data.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Ester derivatives IVa-d were prepared by refluxing the appropriate benzoic acid de rivatives, namely benzoic acid, 2-hydroxybenzoic acid, 2-chlorobenzoic acid, and 4-chlo robenzoic, in pure methanol containing sulfuric acid as a catalyst. Refluxing the obtained ester derivatives IVa-d with hydrazine hydrate afforded the corresponding acid hydra zides Va-d [49,50], as shown in Scheme 1. The reaction of hydrazine hydrate with 2,4 dichloroquinazoline III in ethanol and in the presence of TEA at 0-5 °C afforded the targe compound 2-chloro-4-hydrazinyl3,4-dihydroquinazoline VI [51,52].…”
Section: Chemistrymentioning
confidence: 99%
“…The recent statistics shown that hydrazones are the new, promising molecules for clinical therapy of epilepsy [14][15][16][17] . Not only do hydrazones have anticonvulsant potency, but have reported anti-inflammatory and analgesic 18 , antimicrobial 19 and antitubercular [20][21] . In this study, novel hydrazone compounds with pharmacophore will be tested by the standard protocols at different dosage and see whether they reflect high efficacy and even more acceptable health complications.…”
Section: Introductionmentioning
confidence: 99%